Angles, Traction, and Time after Delivery of Fetal Head: Interobserver Variation of Novel Visual Analogs - Ankumah, Nana-Ama E.; Chauhan, Vidya B.; Pedroza, Claudia; McLaren, Rodney M.; Blackwell, Sean C.; Chauhan, Suneet P. (American Journal of Perinatology, 2017)
Objective The objective was to ascertain interobserver variability for assessment of Angles of fetal head manipulation, Traction exerted on the fetal head, and Time interval from the emergence of the head to the feet (ATT) at vaginal delivery.Materials and Methods Singleton pregnancies of ≥36 weeks with vaginal delivery were included. Visual analogs were created to assess angles and traction, and mobile phone stopwatch was used to assess the time interval. The intraclass coefficient (ICC) was calculated to determine interobserver variability.Results Thirty-seven deliveries were analyzed. For the two observers, the median angle for downward manipulation was –5° vs –20° (interquartile range [IQR], –5 to –5 vs –30 to –10), ICC of 0.09 (poor agreement; 95% confidence interval [CI] –0.09, 0.32), and that for upward manipulation was 10° vs 20° (IQR, 10–15 vs 10–30), ICC of 0.25 (poor agreement; 95% CI –0.05, 0.52). ICC for lateral manipulation could not be calculated as it was not noted in 98% of deliveries. Mean traction was 2.5 versus 5.0, ICC of 0.36 (poor agreement; 95% CI –0.09, 0.72). The mean time intervals were 14.9 versus 14.0 seconds, ICC of 0.94 (excellent agreement, 95% CI 0.88–0.97).Conclusion With exception of time interval, interobserver agreement was poor in estimation of fetal head manipulation and traction.
Keywords: shoulder dystocia; neonatal brachial plexus palsy; traction; vaginal delivery